Identification of 'Voodoo': an emerging substance of abuse in Egypt. Issue 1 (2nd January 2022) - Hussien, Rania; Ahmed, Sarah; Awad, Hanem; El-Setouhy, Maged; El-Shinawi, Mohamed; Hirshon, Jon Mark
ABSTRACT: Background : 'Voodoo' is a new substance of abuse that recently spread among youth in Egypt. It has numerous potentially dangerous effects on humans. However, to date the composition of the main constituents of this compound is unknown. Purpose : We sought to identify the active components of this unknown substance"voodoo". Methods : Three samples were collected and analysed by high-performance liquid chromatography with photodiode array detector (HPLC-PAD), gas chromatography/mass spectrometry (GC/MS), and ultra-performance liquid chromatography/mass spectrometry (UPLC-MS/MS) using targeted multiple reaction monitoring (MRM). Results : HPLC-PAD analysis showed that samples 1 and 2 had some common major peaks, the same retention time, and similar spectra, whereas sample 3 showed different peaks. GC/MS analysis revealed the presence of various putatively identified bioactive compounds, including quinazolines, morphinan alkaloid, cannabinoids, penitrem A, and the well-known synthetic cannabinoid FUB-AMB (methyl(2S)-2-[1-[(4-fluorophenyl)methyl]indazole-3-carbonyl]amino-3 methylbutanoate). UPLC-MS/MS analysis revealed the presence of common compounds such as tetrahydrocannabinol (THC), amphetamine, 3, 4-methylenedioxyamphetamine, tramadol, and oxazepam. Conclusion : We concluded that Voodoo is a mixture of substances of abuse at varying concentrations.